Addressing predictors of HIV related risk behaviors: Demographic and psychosocial profile of Iranian patients - Zohreh Zandmomen; Sara Sardashti; Mona Mohammadi Firouzeh; Fatemeh Jahanjoo Aminabad; Hamed Ghanbariragheb; SeyedAhmad SeyedAlinaghi; Minoo Mohraz (Elsevier, 2014)
Summary: Background: For effective implementation of HIV-related behavioral interventions, better understanding the demographic characteristics of infected patients in relation with high-risk behavior profiles, physical and mental health are essential. Methods: In a cross-sectional descriptive study, 400 HIV infected patients from December 2011 through January 2013 were evaluated regarding their demographic features, and four selected subscales (high-risk behaviors, self-efficacy, well-being, and social participation). A validated questionnaire of 62 items was used for assessment. Results: Almost 33% of all participants were women, 28% were younger than 30 years old, and 43% were never married; 50% had no permanent jobs. Women, widowed participants, patients <30 years, and those with higher educational levels had higher mean HIV risk behavior scores. In simple and multiple linear regression models, women >50 years and <30 years had the highest scores (β = 2.714, p < 0.0001; β = 2.00, p < 0.001). Furthermore, male and illiterate patients had higher social participation scores while female and divorced participants had higher well-being and self-efficacy scores. Conclusion: We propose that demographic features play a critical role in increasing engagement in HIV-related high-risk behaviors; these characteristics also affect patients' social participation, well-being and self-efficacy. High-risk behaviors and social participation scores among women of different age groups and the youth highlight the need for future age and gender-specific educational and behavioral interventions among them. Keywords: Demographics, Sexual, Behavior, HIV, Psychosocial factors